Subcritical water pre-treatment of palm oil waste co-digestion: physicochemical insights, energy recovery, and economic feasibility - Aili Hamzah, Adila Fazliyana; Hamzah, Muhammad Hazwan; Che Man, Hasfalina; Nurulhuda, Khairudin; Ismail, Muhammad Heikal; Show, Pau Loke; Md Ali, Abd Halim (Elsevier, 2026)
The palm oil industry produces large amounts of empty fruit bunches (EFB) and palm oil mill effluent (POME), creating environmental challenges but offering bioenergy potential. This study assessed subcritical water (SCW) pre-treatment of EFB and its co-digestion with POME, focusing on physicochemical changes, biogas yield, energy balance, and economic feasibility. SCW pre-treatment was conducted at 120–180°C for 10 min at 20:1 water:EFB ratio, followed by mesophilic (37°C) co-digestion via the biochemical methane potential (BMP) method at 11 gVS/L with an EFB:POME ratio of 0.6:1. Results showed that SCW altered EFB structure, reduced silica and potassium, and enhanced fermentable compound release. Within the tested range, pre-treatment at 120°C offered the best trade-off between methane yield and net energy recovery (0.38 MJ, 0.10 kWh). Although methane production increased to 329.6 mL CH4/gVS at 180°C, higher severities reduced energy efficiency due to excessive heat demand. Economic analysis showed SCW integration is viable, yielding USD 7.07 million/year profit, 13% return, an 8-year payback period, and a net present value of USD 34.27 million. Microbial analysis revealed enrichment of hydrolytic bacteria and acetoclastic methanogens, promoting effective substrate degradation. Overall, SCW pre-treatment enhanced EFB biodegradability, biogas productivity, and economic sustainability of co-digestion with POME.